2019
DOI: 10.3197/096327119x15579936382509
|View full text |Cite
|
Sign up to set email alerts
|

Atheism in the American Animal Rights Movement: An Invisible Majority

Abstract: Previous research has alluded to the predominance of atheism in participant pools of the Nonhuman Animal rights movement (Galvin and Herzog 1992; Guither 1998), as well as the correlation between atheism and support for anti-speciesism (Gabriel et al. 2012; The Humane League 2014), but no study to date has independently examined this demographic. This article presents a profile of 210 atheists and agnostics, derived from a larger survey of 287 American vegans conducted in early 2017. Results demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…According to the Judeo-Christian ideology, humans are superior beings who were created in God’s image and who are licensed by God to dominate over other begins. Meanwhile, atheists are overrepresented among those who support animal rights (e.g., Deemer & Lobao, 2011; Peek et al, 1997) or adopt veganism out of concern for animals (Wrenn, 2019). Being more interested in science than religious people are (McPhetres et al, 2021), atheists acknowledge the evolutionary continuity between humans and animals more than God-believers (Templer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Judeo-Christian ideology, humans are superior beings who were created in God’s image and who are licensed by God to dominate over other begins. Meanwhile, atheists are overrepresented among those who support animal rights (e.g., Deemer & Lobao, 2011; Peek et al, 1997) or adopt veganism out of concern for animals (Wrenn, 2019). Being more interested in science than religious people are (McPhetres et al, 2021), atheists acknowledge the evolutionary continuity between humans and animals more than God-believers (Templer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests, in line with vegetarian ecofeminist theory ( Gaard, 2002 ), that patriarchal dualist religions may tie conservative, masculine, and human supremacist identities together in opposing veg*n advocacy. On the other hand, though, religious viewpoints are likely to be diverse; religious people may also view veg*nism as a sign of devotion and spiritual purity ( Wrenn, 2019 ), in line with the Garden-of-Eden ideal ( Bekoff and Meaney, 1998 ). Notably, in India, vegetarianism is part of religious traditions (i.e., Jainism, Hinduism) and vegetarians are more likely to endorse conservative values than omnivores ( Ruby et al, 2013 ).…”
Section: Theoretical Accountmentioning
confidence: 99%
“…The latter observation is unsurprising as there exists a strong correlation between atheism and veganism-in one survey of American vegans more than 50% self-identified as atheists. 17 A study of patients at a US Dermatology centre showed that 74% of patients wanted to know if an animal-derived product would be used on their skin. Furthermore, for 40% of patients, the presence of an animalderived product in their sutures would affect their treatment preferences.…”
Section: Original Researchmentioning
confidence: 99%